Narrative Hermeneutics, History, and Rhetoric : A Festschrift for David P. Moessner - Calhoun, Robert Matthew,; Mitchell, Margaret M.,; Nicklas, Tobias,; Spittler, Janet E., (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2024)
David P. Moessner has pioneered the study of early Christian narrative both through the investigation of the principles and methods of good storytelling outlined by ancient authors, and through the demonstration that Christians, especially the author of Luke-Acts, used these principles and methods in crafting their own stories. The contributors to this volume recognize Moessner's enormously valuable research and warm collegiality with twenty-one essays on narrative hermeneutics, characterization, genre, intertextuality, and reception history. Several focus fittingly on Luke and Acts, while others press the implications of Moessner's work for comprehension of the wider world of Jewish, Christian, and Greco-Roman storytelling.